Review Artikel : Analisa Bahan Kimia Obat Pada Jamu Pegal Linu Yang Tersebar Pada Beberapa Daerah Di Indonesia - Firlie Bastia Putty Zahra; Janwar Janwar; Mita Lianastuti; Sri Ayu Winarti; Siti Nurcahyati; Lia Fikayuniar (Jurnal Ilmiah Wahana Pendidikan, 2023)
Jamu is a traditional Indonesian medicine that comes from plants and non- plant natural ingredients that are served traditionally. Medicinal Chemicals (BKO) are often mixed in herbal products to increase sales results, medicinal chemicals in herbal medicine can produce side effects in the form of gastric perforation and kidney failure. This study aims to identify the presence of medicinal chemicals in herbal medicine for aches and pains in several regions in Indonesia. The method used is a Literature Review and research samples obtained from online searches using the Google Scholar database. The results obtained contained the content of medicinal chemicals in several herbal medicine preparations spread across several regions in Indonesia.